Q: What is the value of 6 over x 2x2 when x 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x2-x-6 = (2x+3)(x-2)

Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3

3/(x2+4x-1) = 6/(2x2-3x+5) Cross - multiply in order to eliminate the fractions: 6*(x2+4x-1) = 3*(2x2-3x+5) 6x2+24x-6 = 6x2-9x+15 6x2-6x2+24x+9x = 15+6 33x = 21 x = 21/33 => x = 7/11

2x2 + 6 = 30 is your statement.2x2 = 24x2 = 12x = ±√12x = ±√(4*3)x = 2√3 or x = -2√3

6

Related questions

4/6 = (2x2)/(2x3) = 2/3

2x2-x-6 = (2x+3)(x-2)

5/6 - 1/6 = 5-1/6 = 4/6 = 2x2/3x2 = 2/3

Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

3/(x2+4x-1) = 6/(2x2-3x+5) Cross - multiply in order to eliminate the fractions: 6*(x2+4x-1) = 3*(2x2-3x+5) 6x2+24x-6 = 6x2-9x+15 6x2-6x2+24x+9x = 15+6 33x = 21 x = 21/33 => x = 7/11

2x2 + 6 = 30 is your statement.2x2 = 24x2 = 12x = ±√12x = ±√(4*3)x = 2√3 or x = -2√3

6/8 = 3/4

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

(2x+3)(x-2)

6

6/7 is greater than 3/4